Pyramidal cells in V1 of African rodents are bigger, more branched and more spiny than those in primates - Elston, Guy; Manger, Paul (Frontiers in Neuroanatomy, 2014)
Pyramidal cells are characterized by markedly different sized dendritic trees, branching patterns, and spine density across the cortical mantle. Moreover, pyramidal cells have been shown to differ in structure among homologous cortical areas in different species; however, most of these studies have been conducted in primates. Whilst pyramidal cells have been quantified in a few cortical areas in some other species there are, as yet, no uniform comparative data on pyramidal cell structure in a homologous cortical area among species in different Orders. Here we studied layer III pyramidal cells in V1 of three species of rodents, the greater cane rat, highveld gerbil, and four-striped mouse, by the same methodology used to sample data from layer III pyramidal cells in primates. The data reveal markedly different trends between rodents and primates: there is an appreciable increase in the size, branching complexity, and number of spines in the dendritic trees of pyramidal cells with increasing size of V1 in the brain in rodents, whereas there is relatively little difference in primates. Moreover, pyramidal cells in rodents are larger, more branched and more spinous than those in primates. For example, the dendritic trees of pyramidal cells in V1 of the adult cane rat are nearly three times larger, and have more than 10 times the number of spines in their basal dendritic trees, than those in V1 of the adult macaque (7900 and 600, respectively), which has a V1 40 times the size that of the cane rat. It remains to be determined to what extent these differences may result from development or reflect evolutionary and/or processing specializations.